Association of secondary metabolite gene clusters with host-specific lineages of the cereal blast fungus Pyricularia oryzae - Khyati Mehta; Jorge C. Navarro-Muñoz; Sayali Bakore; Jérôme Collemare; Rajesh Patkar (Phytopathology Research)
Abstract Fungal plant pathogens constantly evolve and deploy novel peptide and metabolite effectors to break down plant resistance and adapt to new host plants. The blast fungal pathogen Pyricularia oryzae is a single species subdivided into multiple host-specific lineages that have evolved through gain and/or loss of virulence and/or effector related genes through chromosomal rearrangement. Here, we mined 68 genomes of P. oryzae, belonging to six host-specific lineages, to identify secondary metabolite (SM) biosynthetic gene clusters (BGCs) likely associated with potential metabolite effectors involved in host specialization. A similarity network analysis grouped a total of 4501 BGCs into 283 gene cluster families (GCFs), based on the content and architecture of the BGCs. While most of the GCFs were present in all the P. oryzae lineages, two (BGC-O1 and BGC-O2) were found specifically in the Oryza lineage and one (BGC-TLE) was found in the lineage specific to Triticum, Lolium, and Eleusine hosts. Further analysis of the phylogenetic relationships between core biosynthetic genes confirmed that BGC-O1, which comprises a reducing polyketide synthase gene (MGG_08236) and four putative tailoring genes, was present only in the Oryza lineage. Importantly, most genes, including MGG_08236 from the BGC-O1, were expressed specifically during pathogenesis. We propose that the Oryza lineage-specific BGC-O1 produces a metabolite effector likely involved in specialization of P. oryzae to the rice host. In addition, we identified five SM genes under positive or balancing selection only in the Oryza lineage, suggesting a role in the interaction with rice specifically. Our findings highlight the importance of further mining novel metabolite effectors in specialization and virulence of the blast fungus to different cereal hosts.